Yuzu the Pet Vet - Book 2 3 - Ito, Mingo; Goniwich, Julie; Yoo, David, (Cartoonist) (New York : Kodansha Comics, 2020)
Every day is a learning experience for 11-year-old Yuzu. Between visiting her mom at the hospital, and helping out at her uncles animal hospital, shes starting to get the hang of what it means to care! This time Yuzu meets a pup that goes from spoiled to smart, as well as a super-smiley therapy dog. She also discovers how hard it is to adjust to new siblings -- fuzzy or otherwise! Later, after meeting an elderly cat, Yuzu learns what "quality of life" is, and just how important it is to listen to what our pets tell us.
Translated from the Japanese.
Keywords: Preteen girls; Japan; Comic books, strips, etc; Veterinary hospitals; Comic books, strips, etc; Veterinarians; Comic books, strips, etc; Human-animal relationships; Comic books, strips, etc; Friendship; Comic books, strips, etc; Comics (Graphic works); Graphic novels; Graphic novels; Comics (Graphic works); Fiction